Bio-Glycerol Synthesis and Characterisation from Palm Kernel Seed Oil of Cameroon - Alang, Michael Bong; Kor, Ndikontar Maurice; Ndifon, Peter T. (Chemistry and Biochemistry: Research Progress Vol. 6, 2025)
A good fraction of glycerol used for industrial and research applications is produced from fossil fuel sources through various synthetic routes. Owing to the fact that petroleum is a nonrenewable source of energy and fossil fuels are gradually undergoing extinction, more research is tilted towards renewable energy sources, which have greater technological, environmental and health advantages. Hence, in this study, bio-glycerol was synthesised from Cameroon palm kernel oil (PKO) through the transesterification procedure. Some essential materials in this study included palm kernel seeds obtained from the Widikum sub-division of the North West region of Cameroon, a mechanical press for vegetable oil extraction, Soxhlet extractor used for more efficient oil extraction of palm kernel oil from seeds. Palm kernel oil was extracted from palm kernel seeds by employing a mechanical expeller and solvent extraction. The Soxhlet apparatus was used to extract palm kernel seed oil, targeting a more accurate percentage oil content determination of palm kernel seeds. Using the mechanical press, the oil, and the percentage oil content shall be less accurate as the press-cake contains non-zero quantities of palm kernel seed oil. The palm kernel oil was purified and characterised by physico-chemical methods and used in the transesterification process to give biodiesel and bio-glycerol. The biodiesel was purified and characterised as reported in previous study in this research series. Our focus in this study is on glycerol, an important by-product of the transesterification process, which has potential pharmaceutical, cosmetic and engineering applications. The bio-glycerol was purified by acidification, and the purified glycerol was subjected to physical and chemical characterisation. The specific gravity of glycerol was obtained as 1.2 kg/L, viscosity at 40oC gave 1500 cSt and 500 cSt at 100oC; pH was 7.4; the flash point was 160oC, and the ASTM colour was 2.0 before purification and zero after purification. The sulfur content was 0.016%w/v. This sulfur content is low, thus posing no environmental threat. The chemical composition of the synthesised bio-glycerol, determined using IR spectroscopy and gas chromatography-mass spectrometry (GC-MS), confirmed the known chemical structure of glycerol. Some impurity molecules present in the bio-glycerol synthetic mixture may come from glycerol fragments and other molecular fragments in the transesterification medium due to oxidative and slight polymerisation processes in the reaction medium. The purification and analysis of bio-glycerol is important as it can find applications in the pharmaceutical, cosmetic and food industries inter alia. Apart from the existing industries that currently make use of glycerol, the development of more innovative technologies for the conversion of crude glycerol to new products needs to be encouraged. Hence, obtaining bio-glycerol from palm kernel seed oil further enhances industrial waste minimisation, environmental sanitisation, and cost-effective manufacturing in Africa in general and Cameroon in particular.